Roberts Syndrome: A Case Report - Arumsari, Regina; Prawitasari, Shinta; Attamimi, Ahsanudin (JURNAL KESEHATAN REPRODUKSI, 2025)
Background: Roberts syndrome (RBS) is a rare autosomal recessive disorder, with no estimates of prevalence have been published. It is caused by mutation in the “Establishment of cohesion 1 homolog 2” (ESCO2) gene on the short arm of chromosome 8, and characterized by symmetrical limb reduction, craniofacial anomalies, growth retardation, mental retardation, cardiac, and renal abnormalities.Objective: The aim of this case report is to describe the findings of a suspected case of Roberts syndrome born at Dr. Sardjito General Hospital and to examine the diagnostic process in suspected cases of Roberts syndrome in low-income countries such as Indonesia.Case: A 32-year-old woman came to the hospital at 29 weeks' gestation. Antenatal sonography screening showed a singleton pregnancy with multiple congenital anomalies: labiognatopalatoschisis, short humerus with absent antebrachial structures. After counseling about the fetal condition and prognosis, the pregnancy was terminated by Misoprostol induction. Post-natal examination revealed an extremely low birth weight baby with labiopalatoschisis, ear malformation, ventricular septal defect, patent foramen ovale, diaphragmatic eventration, bilateral phocomelia, syndactyly, and a Congenital Talipes Equinovarus (CTEV) of the left foot. A Roberts syndrome was suspected, and a cytogenetic testing was initially planned, however it was not done due to the high cost of the test and its availability. The baby’s condition deteriorated and later died on the second day after birth.Discussion: A suspicion of Roberts syndrome may begin during prenatal ultrasound of a fetus with multiple congenital anomalies. Mortality rates are high in severe clinical manifestations. Follow-up management for survivors involves a multidisciplinary medical approach.Conclusion:  Prenatal findings of limb abnormalities should be evaluated carefully to detect any associated anomalies which may links to a specific syndrome, thus helping a clinician predict prognosis, and further decide the most beneficial patient management.